پاکستان میں صنفی تشددکی نوعیتیں اور ان کا سدباب :اسلامی تناظر میں تنقیدی جائزہ: Types of Gender-Based Violence in Pakistan and its Eradication: A Critical Study in an Islamic Perspective - Muhammad Zia Ul Haq; Malaeka Umer khan (AL-IDRAK JOURNAL, 2024)
Gender based violence marginalizes its victims and survivors. They may feel helpless and inferior. Gender-based crimes have various forms and types. From honour killing to harassment, a long list of various types of GBV is found around the globe. Some of the types are universal and others are regional or country-specific. The effective provision of gender equality is central to safeguarding from this violence. Protection of human rights, upholding the rule of law and true democracy are among the strong factors for the provision of gender justice and protection from gender-based violence. Gender equality and gender justice cannot be achieved without equality in visibility, empowerment and opportunities. Gender equality also implies equal access of all genders to the resources of the state. An effective institutional framework for protection, preservation and provision of justice for the victims of GBV is a symbol of a civilized society. A society can eradicate this problem only after the adoption process of social civilization. All these issues are critically evaluated in this study.To better facilitate investigation on various types of GBV in Pakistan, the study discussed issues such as honour killing and other honour-related crimes, problems in reporting honour crimes, domestic violence, sexual harassment, rape and sexual assault, acid burnings, digital violence or virtual violence and the relationship between health and GBV. The study also proposed framework for eradication and reduction of these types of GBV in Pakistan in the perspective of Islam. The role of Islamic teaching in eradication of female infanticide and state of eunuchs in Islamic society is also part of study.